2023
DOI: 10.51966/jvas.2023.54.1.59-63
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of growth responses of Wistar rats fed with a diet containing composite flour premix

Abstract: Composite flour technology involves the process of mixing cereals and legumes to facilitate the usage of locally available raw materials to produce high-quality food products economically. The present investigation evaluated the growth responses of a composite flour blend formulated using selected cereals, pulses and oil seed (a total of nine grains) were evaluated in two-month-old growing Wistar rats. The feeding trial was conducted for four weeks after an acclimatization period of five days. Daily feed intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
1
Order By: Relevance
“…However, they reported that the yellowness of the composite flours decreased, contrary to the findings reported in this study [15]. The colour of flours is pertinent to their acceptability and potential use [16]. The bulk densities of the samples (Table 1) ranged from 0.50-0.55 kg/m 3 for loose bulk density and 0.70-0.77 kg/m 3 for packed bulk density.…”
Section: Colour Parameters Of Wheat and Aerial Yam Composite Flourscontrasting
confidence: 85%
“…However, they reported that the yellowness of the composite flours decreased, contrary to the findings reported in this study [15]. The colour of flours is pertinent to their acceptability and potential use [16]. The bulk densities of the samples (Table 1) ranged from 0.50-0.55 kg/m 3 for loose bulk density and 0.70-0.77 kg/m 3 for packed bulk density.…”
Section: Colour Parameters Of Wheat and Aerial Yam Composite Flourscontrasting
confidence: 85%